Answer:
D
Step-by-step explanation:
So we have the expression:
![(3x^2-5x+6)+(9-8x-4x^2)](https://tex.z-dn.net/?f=%283x%5E2-5x%2B6%29%2B%289-8x-4x%5E2%29)
Combine like terms:
![=(3x^2-4x^2)+(-5x-8x)+(6+9)](https://tex.z-dn.net/?f=%3D%283x%5E2-4x%5E2%29%2B%28-5x-8x%29%2B%286%2B9%29)
Add or subtract:
![=(-1x^2)+(-13x)+(15)](https://tex.z-dn.net/?f=%3D%28-1x%5E2%29%2B%28-13x%29%2B%2815%29)
Simplify:
![=-x^2-13x+15](https://tex.z-dn.net/?f=%3D-x%5E2-13x%2B15)
Our answer is D
Answer: a) {-3, -1, 3, 4}
Step-by-step explanation:
f(x) is the output, and x is the input.
Hope it helps :) and let me know if you want me to elaborate.
It’s %25 off think about it 40-10=30 and that’s %25 of it hope I help you have a good day
The right question is that the lowest altitute is 3^8 feet
You are told that the highest altitude is 3 times the lowest altitude =>
highest altitude = 3 * lowest altitude = 3 * 3^8 feet.
Now you use the ruel of mutiplication of powers with the same base: copy the base and sum the exponents => 3 * 3^8 = 3 ^(1+8) = 3^9.
Note: remember that 3 = 3^1.
Answer: 3^9 feet
Answer:
It's basically already in order: 0.57, 5.07, 50.7, 57, 75
Step-by-step explanation:
Hope it helps! :3
Plz mark as brainliest!